"Sego Gono" as a Culinary Tourism Attraction in Temanggung Regency, Central Java - Farizqi, Muhammad Yustidar; Prasetyanto, Hermawan (Gastronary, 2025)
Temanggung has a diverse array of local cuisine, ranging from traditional dishes to contemporary ones. One notable traditional food item is called ‘Sego Gono,’ which has been passed down through generations and holds its own unique historical significance. While it serves not only as part of Indonesia's rich culinary heritage but also as a cultural symbol for the people of Temanggung, it remains underappreciated as a culinary touristic attraction. Given this background, the purpose of our research is to delve into the history of Sego Gono, explore how it is prepared, analyze whether it could serve as a draw for culinary tourists in Temanggung, and examine the gastronomic aspects inherent within Temanggung’s traditional cuisine. Our methodology involves qualitative descriptive research methods combined with data collection techniques such as interviews with practitioners of cooking, experts in gastronomy, historians, and literature studies to understand the origins of Sego Gono as a specialty dish in Temanggung. Data analysis will involve reduction, presentation, and conclusion drawing. Our findings conclude that ‘Sego Gono’ has potential as both a tourist attractor and a developmental tool for culinary tourism in Temanggung, given its historical value and philosophical depth. It can be promoted as a destination for gastronomic tourism while providing additional knowledge for consumers or travelers enjoying their meals there. Furthermore, recognizing Sego Gono as a local specialty can enhance storytelling among visitors, thereby boosting economic values within the tourism industry in Temanggung.